Development of A Clinical Decision Support System for Calculus Risk Prediction - Marlindayanti, Marlindayanti; Dyah Utami, Wahyu Jati; Baizan , Annisa; Tsaliza Muntazi , Yasmin; Sepriani , Putri; ’Atun, Qori (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Oral health in Indonesia remains a significant problem, with 57.6% of the population experiencing problems but only 10.2% accessing treatment. Dental calculus is one of the main etiologies of periodontal disease. Therefore, healthcare professionals require a rapid and standardized screening tool to efficiently identify high-risk patients. This study aims to report the development process and trial results of the